The Measurement of Time-Varying Technical Efficiency and Productivity Change in Polish Crop Farms - Jerzy Marzec; Andrzej Pisulewski (German Journal of Agricultural Economics (GJAE), 2019)
The main aim of this study is to measure the technical efficiency and decompose total factor productivity (TFP) growth of Polish crop farms. The novelty of our contribution is threefold. First of all, our work contributes to research on agricultural performance of Central and Eastern European countries in the post-European Union accession period. Secondly, compared to previous studies, our study expands them by decomposition of total factor productivity growth for a specific sector based on a very extensive dataset, thus providing a more in-depth analysis of factors driving productivity growth. Thirdly, we have thoroughly explored the same data set by several different models, showing consequences of choosing a particular model. The empirical analysis is based on a balanced panel of farms, from 2004 to 2011, taken from the Farm Accountancy Data Network. Findings show that the average technical efficiency was only 63%. The elasticity of production was highest with respect to materials and lowest with respect to area. The capital elasticity was statistically non-significant. We point out that this sector is characterized by increasing returns to scale, with estimates ranging from 1.05 to 1.3 for the majority of observations. Furthermore, the results show that TFP was slightly decreasing (on average by 0.067% per annum) over the entire period.
Keywords: 330